2021
DOI: 10.3390/pathogens10060663
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Multiple Zoonotic Viral Infections among Wild Rodents in Barbados

Abstract: Background: Rodents are reservoirs for several zoonotic pathogens that can cause human infectious diseases, including orthohantaviruses, mammarenaviruses and orthopoxviruses. Evidence exists for these viruses circulating among rodents and causing human infections in the Americas, but much less evidence exists for their presence in wild rodents in the Caribbean. Methods: Here, we conducted serological and molecular investigations of wild rodents in Barbados to determine the prevalence of orthohantavirus, mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Furthermore, serological information by screening antibodies such as immunoglobulin G could help with detecting previous infections, thus providing further insight on the circulation of arenaviruses in Gabon. Indeed, several previous studies support the acute infection model that postulates that small mammals' infection by arenaviruses are normally acute, which means that (i) there is an increase of mortality among infected rodents [28,32,48,49], (ii) viral clearance operates quickly and, (iii) is replaced by antibodies production among survivals [50][51][52]. Thus, tested individuals are positive either by PCR or IgG [53].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, serological information by screening antibodies such as immunoglobulin G could help with detecting previous infections, thus providing further insight on the circulation of arenaviruses in Gabon. Indeed, several previous studies support the acute infection model that postulates that small mammals' infection by arenaviruses are normally acute, which means that (i) there is an increase of mortality among infected rodents [28,32,48,49], (ii) viral clearance operates quickly and, (iii) is replaced by antibodies production among survivals [50][51][52]. Thus, tested individuals are positive either by PCR or IgG [53].…”
Section: Discussionmentioning
confidence: 95%
“…Fowlpox was also noted to be present among poultry populations in Trinidad and Tobago during 1996-1998, 2000-2005 1997-2005(OIE-HANDISTATUS II, 2005OIE-WAHIS, 2020). A recent study from Barbados found orthopoxvirus by immunofluorescence assay (IFA) in 7.5% of sampled rodents (Douglas et al, 2021).…”
Section: Poxviridaementioning
confidence: 99%
“…Barbados documented fowlpox in 1996–1997, 1999–2002 and 2004–2005 (OIE‐HANDISTATUS II, 2005; OIE‐WAHIS, 2020). A recent study from Barbados found orthopoxvirus by immunofluorescence assay (IFA) in 7.5% of sampled rodents (Douglas et al., 2021).…”
Section: Dna Viruses Circulating In Terrestrial Animals In the Caribb...mentioning
confidence: 99%
See 2 more Smart Citations